Students’ Perception of the Use Serial-Image as an English Learning Media - Aryanika, Septa; Zakiyah; Isna, Nur Kamila (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study investigated students’ perceptions of serial-image media in English reading instruction at SMP Al Kautsar Bandar Lampung during the 2024/2025 academic year. Employing a quantitative descriptive method with a non-experimental survey design, data were collected from 96 ninth-grade students selected through purposive sampling. A closed-ended questionnaire consisting of 20 items, validated using Pearson Product Moment and tested for reliability with Cronbach’s Alpha (α = 0.892), was administered to measure four aspects: learning process and skill development, direct experience, challenges, and general perception. Findings revealed that students demonstrated a generally positive perception of serial-image media. The highest mean score was found in the aspect of learning process and skill development (M = 3.77), followed by direct experience (M = 3.71), challenges (M = 3.34), and general perception (M = 3.33). Students reported that serial images facilitated comprehension, enriched vocabulary, and stimulated classroom engagement, though some noted difficulties with unclear visuals. These results support Mayer’s Cognitive Theory of Multimedia Learning, emphasizing the benefits of integrating verbal and visual modalities. The study suggests that serial images are effective supplementary tools for enhancing reading comprehension and encourages their integration with teacher guidance and interactive methods.